Foreign Policy of European Union: Eurasian Agenda - Oleksiy Kandyuk (CES Working Papers, 2016)
EU's influence at so-called post-Soviet space gradually increases and becomes a significant factor of regional policy. Today we can already speak of the European Union as a full participant in the political processes occurring in the post-Soviet and broader – Eurasian area. Foreign policy of EU is evolving under impact of reasons stemming from both structural and political context and from external geopolitical trends. At the same time, challenges in the geopolitical environment in Europe today require the EU to develop new conceptual approaches helping to deal with the problems of relations with its eastern neighbours and the Russian impact. Only the development of a new Eurasian agenda could help to improve European eastern policy, consolidate the position of EU as a geopolitical actor in this region and foster Europeanization and integration of neighbour countries.
Keywords: 330; European integration; Foreign policy of EU; European neighbourhood policy; Eastern partnership